Quantitative analysis of biofluid spots by coated blade spray mass spectrometry, a new approach to rapid screening - Boyaci, Ezel; Gómez-Ríos, Germán Augusto; Pawliszyn, Janusz; Poole, Justen J.; Tascon, Marcos; Reyes-Garcés, Nathaly (Springer Nature, 2017)
This study demonstrates the quantitative capabilities of coated blade spray (CBS) mass spectrometry (MS) for the concomitant analysis of multiple target substances in biofluid spots. In CBS-MS the analytes present in a given sample are first isolated and enriched in the thin coating of the CBS device. After a quick rinsing of the blade surface, as to remove remaining matrix, the analytes are quickly desorbed with the help of a solvent and then directly electrosprayed into the MS analyzer. Diverse pain management drugs, controlled substances, and therapeutic medications were successfully determined using only 10 µL of biofluid, with limits of quantitation in the low/sub ng·mL−1 level attained within 7 minutes.
Keywords: Bioanalytical chemistry; Laboratory techniques and procedures; Pain management